Analisis Tekno Ekonomi Pengembangan Jalur Kereta Api Rencana Areal Terminal Untuk Kepentingan Sendiri Pelabuhan Panjang - komang rania; Ika Kustiani; Amril Ma’ruf Siregar (REKAYASA: Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2025)
Lampung is one of the provinces traversed by railway lines with mainstay train transportation, namely coal, fuel oil, pulp, and passenger transportation. The route used is the active route from Tanjung Enim-Tarahan. Along with that, there are several passive railway lines, one of which is the Pidada-Pelabuhan Panjang line. One of the impacts of the high level of road damage in Lampung is that transport is brought to Panjang Harbor via land transport (trucks and containers), so that the presence of rail transport can reduce road damage and environmental pollution. The aim of this research is, among other things, to find out, study and calculate the level of investment feasibility based on techno-economic parameters in the development of railway lines in the planned TUKS area at Panjang Harbor. This research is quantitative research using technical drawing data, RAB, Work Unit Price Analysis, and train fares obtained from PT. Indonesian Railways Lampung Province. Techno-economic analysis in the form of financial and economic feasibility is reviewed using the parameters NPV, IRR, BCR, and PP. The results of the analysis of the feasibility level of investment for developing a railway line in the TUKS area of Panjang Harbor show that the NPV, IRR, BCR, and PP values are positive and can be continued to the planning stage.